10 likes | 113 Views
HW3. S10.1P704#68: Hyperbola S10.1P704#70: Parabola S10.1P704#72: Parabola S10.1P704#74: 2x 2 - 2xy =3y-y 2 - 2xy -> Ellipse S10.1P704#76: Ellipse S10.2P716#4: t=(3-x)/2 = (y-2)/3 -> 9-3x=2y-4 -> 3x+2y=13 S10.2P716#6: t 2 =x/2, y=(x/2) 2 +1 -> x 2 = 4(y-1) [x ≥ 0]
E N D
HW3 S10.1P704#68: Hyperbola S10.1P704#70: Parabola S10.1P704#72: Parabola S10.1P704#74: 2x2-2xy=3y-y2-2xy -> Ellipse S10.1P704#76: Ellipse S10.2P716#4: t=(3-x)/2 = (y-2)/3 -> 9-3x=2y-4 -> 3x+2y=13 S10.2P716#6: t2=x/2, y=(x/2)2+1 -> x2 = 4(y-1) [x≥0] S10.2P716#10: t=x4 -> y=3-x4 [x≥0] S10.2P716#42: (x-h)/a=sec t = 1/cos t -> cos t = a/(x-h). (y-k)/b=tan t= sin t / cos t = sqrt[1-a/(x-h)2] / a/(x-h) -> [(x-h)/a]2 – [(y-k)/b]2= 1